Fruit jelly marmalade recreational purposes - Bashta (Sheremet), Alla; Leschinska, Т. (My University, 2013)
This work is devoted to development of a process of obtaining the fruit and jelly marmalade with pectin as structurant, gelling apple and rhubarb sauce enriched by fruit juice and black elderberry and extracts of herbs (thyme, oregano and violet).
Keywords: marmalade; fruit juice elderberry; water and alcoholic extracts of Thyme; мармелад; сік плодів бузини; водно-спиртові екстракти чебрецю; сок плодов бузины; водно-спиртовые экстракты тимьяна; oregano and viola tricolor; материнки та фіалки триколірної; душицы и фиалки трехцветной; кафедра технології оздоровчих продуктів